Performance of Two Photoscreeners Enhanced by Protective Cases - Martin, Samuel Joseph (Clin Ophthalmol, 2020)
BACKGROUND: Photoscreeners provide valid, cost-effective early detection of amblyopia risk factors﻿; however, they require proper illumination, flash intensity, pupil dilation and patient cooperation. The Kaleidos case for the 2WIN infrared photoscreener fixes focal distance, decreases luminance and provides electric power. GoCheck Kids (GCK) has developed a flash-concentrating case for the Apple iPhone 7 Plus smartphone to reduce exposure time. METHODS: In remote Burm﻿ese and urban Alaskan clinics, Kaleidos and GCK were used before a confirmatory eye examination using 2013 AAPOS uniform guidelines validation, including some older patients. 2WIN refraction was compared to a cycloplegic examination using J0 and J45 vector transformation. RESULTS: In total, 48 Burm﻿ese patients and 114 Alaskan patients aged 8±6 years were evaluated utilizing 2013 amblyopia risk factor guidelines. Kaleidos, with 13 Burmese inconclusives, had a sensitivity of 84%, specificity of 65% and positive predictive value (PPV) of 63%. GCK, with only six inconclusives, had a sensitivity of 63%, specificity of 83% and PPV of 73%, with sensitivity improving to 74% with central expert interpretation. Kaleidos closely matched cycloplegic refraction, with ﻿intraclass correlations of 0.47 for J0 vector and 0.57 for J45 vector. The protective cases provided clearer images and better pupil dilation than similar devices without cases. CONCLUSION: Both devices detected amblyopia risk factors well. GCK gave fewer inconclusive results even with the Asian eyelid configuration, while Kaleidos matched sphere and cylinder refraction. The specialized housing enhanced the performance of the 2WIN and GCK photoscreeners, improving the speed and reliability of amblyopia screening and refraction, even in populous and luminous locations. CLINICAL TRIALS REGISTRY: NCT04068129.